Mediasi Sebagai Alternatif Penyelesaian Sengketa Perdata di Pengadilan (Analisis Putusan Nomor. 52/PDT.G/2015/PN.RAP) - Hikmah, Nur; Minin, Darwinsyah; Isnaini, Isnaini (ARBITER: Jurnal Ilmiah Magister Hukum, 2019)
Peace is the most gentle answer as well as a win-win solutin, the existence of the basic law of mediation in Indonesia as an alternative to the dispute resolution outside the court can be seen in Article 130 HIR and Article 154 RBG which has set up a peace institution which then judges shall first reconcile the parties before the case is reviewed, as described in Article 130 HIR / 154 RBG and PERMA Number. 01 of 2008 on Mediation Procedures in Courts. The formulation of the problem is how the rules of mediation law as an alternative to the settlement of civil disputes in the Court, how the implementation and mechanism in the selection of Mediators at the District Court Rantauprapat and how the results of mediation on civil cases Number.52 / Pdt.G / 2015 / PN.Rap generated from the mediation process, the aim is to know and simultaneously find the law of mediation as an alternative to civil disputes settlement in the Court and to know the implementation and mechanism of the selection of Mediator in Rantauprapat District Court and meganalisis the decision of civil case Number.52 / Pdt.G / 2015 / PN.Rap resulting from the mediation process